(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article examines the emergence of information and communication technologies as a new paradigm for ensuring public safety in today’s rapidly developing modern world, and its connection with the implementation of state security policy. It also studies the central role of digital technologies in most developed foreign countries, in other words, modern technologies are seen as an objective necessity (legitimacy) in ensuring public safety and protecting citizens. Annotation: V state rassmatrivaetsya vozniknovenie informatsionno-kommunikationnyx teknologi kak novoy paradigmy obespecheniya obshchestvennoy bezopasnosti v sovremennom stremitelno razvivayushchemsya mire i ee svyaz s realizationatsei politiki gosudarstvennoy bezopasnosti. It was also studied that in the majority of developed foreign countries digital technologies are interested in the central city, in other words, modern information technologies are considered to be of objective necessity (legality) and to ensure the public safety of the state and protect the city. Annotation. This article highlights the fact that the public security system is closely related to social processes in a given area, and is characterized by the simultaneous provision of public security, coordination of public order, and organization of law and order. It also analyzes the need for innovative mechanisms in ensuring public security, primarily to ensure effective cooperation between government bodies and civil society institutions, and the emergence of information and communication technologies as a new paradigm for ensuring public security in the modern world.